Oil palm fibers micromechanics: anisotropic behavior - Hanipah, Suhaiza Hanim; Talib, Ahmad Tarmezee; P Mohammed, Mohd Afandi; Baharuddin, Azhari Samsu; Wakisaka, Minato (Taylor Francis, 2022)
The anisotropic behavior of oil palm fibers (OPF) was investigated using finite element models, which were used to fit experimental data from stalk and mesocarp oil palm fibers under different tensile deformation modes. The experimental results showed damage to oil palm fibers due to deformation, viscoelastic behavior from reduced stress at fixed strain, as well as anisotropic behavior from tensile-twisting tests. In this work, the finite element models were improved from the previous works on the fiber mechanics by including Fung orthotropic and Prony series viscoelastic functions. The developed single-element finite element model agreed with experimental tensile data under cyclic, stress-relaxation, and step-relaxation modes. The modeling parameters from the single element model and information from the experimental work were then used to simulate the deformation of a virtual fiber obtained from µ-CT analysis, as well as its composite model.